2011
DOI: 10.1002/ajmg.a.34030
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of gingival fibromatosis–mental retardation–hypertrichosis (Zimmermann–Laband) syndrome

Abstract: Zimmermann-Laband syndrome (ZLS) is a rare disorder characterized by gingival fibromatosis, hypertrichosis, intellectual disability, and absence and/or hypoplasia of the nails or terminal phalanges of the hands and feet. The syndromic features of ZLS are highly variable and can overlap with other entities featuring gingival fibrosis. This study describes a patient with ZLS with novel findings, including colpocephaly, hemivertebra, polydactyly, hyperpigmentation, and hemihyperplasia. Thus, the present report ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Castori et al [] reviewed 52 patients. Of these, three had ST [Chadwick et al, ; Holzhausen et al, ; Chacon‐Camacho et al, ], ranging from one to five in number. We conclude that this is probably a chance finding in a condition where gingival‐related issues make dental radiographs, and the consequent ascertainment of coincidental ST more likely.…”
Section: Exclusions Of Commonly Cited Syndromesmentioning
confidence: 99%
“…Castori et al [] reviewed 52 patients. Of these, three had ST [Chadwick et al, ; Holzhausen et al, ; Chacon‐Camacho et al, ], ranging from one to five in number. We conclude that this is probably a chance finding in a condition where gingival‐related issues make dental radiographs, and the consequent ascertainment of coincidental ST more likely.…”
Section: Exclusions Of Commonly Cited Syndromesmentioning
confidence: 99%
“…Literature review showed that the main features of the syndrome are gingival hypertrophy associated with nails or terminal phalanges hypo/aplasia (100% of patients). [43][44][45][46][47][48][49][50] In more than 50% of the patients, a typical facial appearance is detectable, characterized by thick ears, large and bulbous nose, and thick lips with or without macrostomia. Common reported clinical features are moreover ID (more than 40%), joints hypermobility (48%), hypertrichosis of the face and/or the body (37%), hepatosplenomegaly (27%), and seizures (13%).…”
Section: Zimmermann-laband Syndromementioning
confidence: 99%
“…50 Clinical variability is wide even in the same family, and, as commonly observed, the seriousness of the somatic involvement often does not correlate with the severity of the ID. Several other rarer signs have been reported, as pigmentation disorders, 43,49 supernumerary teeth, 45,46,49 ocular anomalies, 47,49 and others. 44,48,49 This wide spectrum of clinical presentations of ZLS reported in the literature could be partly due to the absence, to date, of any confirmatory diagnostic test aimed at clearly defining the ZLS phenotype as compared with the overlapping conditions (DOOR and Cantù syndromes).…”
Section: Zimmermann-laband Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…From 11 affected individuals, all of the four examined males had severe hypertrichosis associated with scoliosis (plus spina bifida in one case only), whereas all affected females had only mild hypertrichosis. Another group of patients with less dense and extensive CGHT show mostly multiple congenital abnormalities of greater severity and compromised life expectancy [1,[24][25][26][27][28][29][30]. These may include autosomal dominant diseases, such as Cantú syndrome, Cornelia de Lange syndrome, Barber-Say syndrome, Schinzel-Giedion syndrome and Zimmermann-Laband syndrome (table 2), and autosomal recessive diseases with a very early onset of severe insulin resistance and acanthosis nigricans, such as Rabson-Mendenhall syndrome, Donohue syndrome and Berardinelli-Seip syndrome (table 3).…”
Section: Group 3: X-linked Cghtmentioning
confidence: 99%